2017
DOI: 10.18869/acadpub.jpcp.5.3.203
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Cognitive-Behavioral Group Therapy on Guilt Feeling Among Family Caregivers of Patients With Alzheimer’s Disease

Abstract: Objective: This study aimed at investigating the effectiveness of cognitive-behavioral group therapy on guilt feeling among family caregivers of patients with Alzheimer's disease. Methods:This research was a quasi-experimental study where in the pre-test and post-test control group design was employed. The statistical population of this study consisted of the female family caregivers of the Alzheimer's patients who were referred to the Iran Alzheimer's Association in 2012. Among this population, 32 volunteers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…46 Few dementia caregiving interventions have targeted and measured specific emotions or affect beyond distress and anxiety. An exception CBT 47 and interventions that incorporate aspects from Acceptance and Commitment Therapy and Compassion-Focused Therapy 48 have been found to decrease care partner guilt. Another example is a positive emotion regulation intervention called Life Enhancing Activities for Family caregivers that improved positive emotions (i.e., a composite including interest, enjoyment, awe, gratitude, hope, and love).…”
Section: Emotional and Affective Experiences In Persons Living With D...mentioning
confidence: 99%
“…46 Few dementia caregiving interventions have targeted and measured specific emotions or affect beyond distress and anxiety. An exception CBT 47 and interventions that incorporate aspects from Acceptance and Commitment Therapy and Compassion-Focused Therapy 48 have been found to decrease care partner guilt. Another example is a positive emotion regulation intervention called Life Enhancing Activities for Family caregivers that improved positive emotions (i.e., a composite including interest, enjoyment, awe, gratitude, hope, and love).…”
Section: Emotional and Affective Experiences In Persons Living With D...mentioning
confidence: 99%
“…The results of this study indicated that there was no signi cant difference between mean scores of knowledge and practice in male and female caregivers; however, in some other studies, it has been pointed out that women's knowledge background from dementia is less than that of men (29). Therefore, studies show that interventional programs are necessary and cost-effective for improving the caregiving process (29,30). Therefore, it is recommended to differentiate between the type, method, and content of educational programs for male and female caregivers.…”
Section: Discussionmentioning
confidence: 62%
“…Overall, the findings from our study and previous research highlight the importance of providing education, training, and support to caregivers of PWD. Interventions that are tailored to the specific needs and cultural context of the population being served can be particularly effective, and may be necessary to improve the caregiving process and promote better outcomes for both patients and caregivers 20,21 . The educational intervention included training the caregivers in communication skills to improve the caregiving process and reduce negative emotions.…”
Section: Discussionmentioning
confidence: 99%
“…Show respect for the patient's religious beliefs and may be necessary to improve the caregiving process and promote better outcomes for both patients and caregivers. 20,21 The educational intervention included training the caregivers in communication skills to improve the caregiving process and reduce negative emotions. The use of a variety of teaching methods can help engage caregivers and make the material more accessible and relevant.…”
Section: Modify Environments To Support Losses and Enhance Safetymentioning
confidence: 99%